Experimental Study on Damage Breakage Properties of Shaft Lining Concrete under Hydromechanical Coupling - Weipei Xue; Zhishu Yao; Wei Jing; Bin Tang; Gan Kong; Dezhu Xie (Advances in Materials Science and Engineering)
Shaft lining concrete is exposed to a long-term coupled effect of a complex stress environment and high underground water pressure. To study the damage breakage properties under the above specific working conditions, shaft lining concrete specimens meeting the requirements of engineering application were prepared. The triaxial hydraulic coupling permeability test was conducted, and the designed osmotic pressures were 4 MPa, 6 MPa, 8 MPa, and 10 MPa. The results show that as osmotic pressure increases, the peak strength of shaft lining concrete decreases gradually, the surface cracks of specimen increase, and the failure mode is oblique shear failure. According to variation characteristics of permeability-strain and stress-strain curves of shaft lining concrete during loading, it is divided into three stages: compaction stage, sudden increase of permeability stage, and postpeak permeability change stage. In addition, the constitutive model of the shaft lining concrete with the influence of confining pressure and osmotic pressure was established, and the theoretical curve is in good agreement with the test curve. The damage evolution model shows that damage threshold of shaft lining concrete occurs earlier than that of ordinary concrete because of the influence of permeable water, and the damage development of the strain softening stage is particularly rapid.